2011
DOI: 10.5535/arm.2011.35.3.436
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Tracheoesophageal Fistula through Esophageal Diverticulum in Patient Who Had a Prolonged Tracheostomy Tube - A Case Report -

Abstract: Acquired tracheoesophageal fistula through esophageal diverticulum is infrequent. We report tracheoesophageal fistula through esophageal diverticulum in a 55-year-old male who had a prolonged tracheostomy tube during 6 months, and a NG tube during 18 months. He suffered from recurrent pneumonia. He complained of a cough associated with eating, and production of sputum mixed with food. To help evaluate the aspiration to the lung and the cause of aspiration, he was tested using gastrointestinal scintigraphy (gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Isolated reports advocate initial management of nonmalignant TEF with endoscopic treatment, such as stent insertion or clip application. Jung et al (16) described a successfully treatment of a quadriplegia patient with TEF through esophageal diverticulum by clipping under the esophagoduodenoscope on November 10, 2009. Schweigert et al (17) also reported the recovery of three of four patients with benign gastro-tracheobronchial fistula treated by endoscopic stent insertion.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated reports advocate initial management of nonmalignant TEF with endoscopic treatment, such as stent insertion or clip application. Jung et al (16) described a successfully treatment of a quadriplegia patient with TEF through esophageal diverticulum by clipping under the esophagoduodenoscope on November 10, 2009. Schweigert et al (17) also reported the recovery of three of four patients with benign gastro-tracheobronchial fistula treated by endoscopic stent insertion.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of occurrence is thought to be either traction (due to scaring and conditions following chronic inflammation such as TB) or pulsion (due to motility disorders of the oesophagus such as achalasia) and diverticula can be named accordingly. Rarer causes include retained foreign bodies [6, 7] and iatrogenic causes (oesophageal stents [8], gastric bands [9], and tracheostomy tubes [10]). Malignant lesions such as squamous cell carcinoma have also been described as possible cause of oesophageal diverticula [11, 12].…”
Section: Discussionmentioning
confidence: 99%
“…6 Jugn et al reported a case of TEF through esophageal diverticulum in a patient who had a prolonged tracheostomy tube. 7 Other documented causes are tracheostomy, lung transplantation, thyroid resection, thoracic aneurysm repair, esophageal leiomyoma enucleation, mediastinoscopy, and cervical spine surgery. 2,8,9,10,11 Common presentations include cough, recurrent pneumonia, increased secretions, and evidence of gastric aspiration into the trachea while on the ventilator.…”
Section: Discussionmentioning
confidence: 99%